Identification and phylogenetic analysis of two canine coronavirus strains - Junji Gan; Ye Tang; Haifeng Lv; Wenbin Xiong; Xiaoyan Tian (BMC, 2021)
Abstract Canine coronavirus (CCoV), a member of the genus Alphacoronavirus, is an enveloped, single-stranded positive-sense RNA virus that responsible for gastroenteritis in dogs. In this study, two CCoV isolates were successfully propagated from 53 CCoV-positive clinical specimens by serial passaging in A-72 cells. These two strains, CCoV JS1706 and CCoV JS1712, caused cytopathic effects in A-72 cells. The sizes of virus plaque formed by them differed in early passages. Electron microscopy revealed a large quantity of typical coronavirus particles with 80-120 nm in diameter in cell culture media and cytoplasm of infected cells, in which they appeared as inclusion bodies. RT-PCR analysis of S gene indicated that these two isolates were belonged to CCoV IIa subtype. Homology of RdRp, S, M and N proteins between the two strains were 100, 99.6, 99.2 and 100.0%, respectively, whereas they were 99.4-100%, 83.1-95.2%, 88.5-99.2% and 91.9-99.7% identity compared to CCoV II reference strains. Phylogenetic analysis of RdRp, S, M and N protein showed that they were closely related to CCoV II strains. These two subtype IIa isolates will be useful for evaluating the pathogenesis and evolution of CCoV and for developing diagnostic reagents and vaccines.